1959
DOI: 10.1037/h0044764
|View full text |Cite
|
Sign up to set email alerts
|

The use of demographic characteristics in predicting length of neuropsychiatric hospital stay.

Abstract: The ever-increasing number of chronic neuropsychiatric patients represents perhaps the foremost problem in the field of mental health today. Despite recent advances, notably in the fields of chemotherapy and rehabilitation, the burden of the chronic population grows, threatening to overwhelm existing hospital facilities and available professional personnel. This study was conceived as the first step in a three-part plan to: (a) develop an index predictive of chronicity; (b) attempt to isolate and study the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1962
1962
1978
1978

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…A number of investigators have proposed that prognostic studies utilizing differing sets of predictor variables are likely to provide more insight into the factors affecting outcome than single variables taken one a t a time (Lindemann, Fairweather, Stone, Smith, and London, 1959;Pascal, Swenson, Feldman, Cole, and Bayard, 1953). I n view of the recent advances in computer methodology, there are surprisingly few studies which include various sets of demographic as Technology.…”
Section: A Multivariate Approach To Prognosismentioning
confidence: 99%
“…A number of investigators have proposed that prognostic studies utilizing differing sets of predictor variables are likely to provide more insight into the factors affecting outcome than single variables taken one a t a time (Lindemann, Fairweather, Stone, Smith, and London, 1959;Pascal, Swenson, Feldman, Cole, and Bayard, 1953). I n view of the recent advances in computer methodology, there are surprisingly few studies which include various sets of demographic as Technology.…”
Section: A Multivariate Approach To Prognosismentioning
confidence: 99%
“…Lindeniann et nl. (5) found organicity and psychosis assoo4atpd with long-term hospitalization, and neurosis and character disorders with short-term hospitalization. Johiistori and AlcNeal ( 4 ) found psychotic (as opposed to iionpsychotic) diagnosis correlated significantly with length of stay.…”
Section: Predicting L E N G T H O F Psychiathic Hobpitallzation From mentioning
confidence: 99%
“…As a result of these combined factors, the probability of release for such patients is even less than that expected for psychiatric patients who have been hospitalized for periods longer than two years. This conclusion is based on the findings of several studies which have pointed out a marked relationship between age, diagnosis, and length of hospitalization (1–3), and of several other studies which have shown that the release rate declines with increasing length of hospitalization (4, 5). In seeking to improve this situation, Manson (6) compared the demographic characteristics of discharged geriatric patients with those of geriatric patients remaining in the hospital.…”
mentioning
confidence: 95%